Islamic Home Financing through Musharakah Mutanaqisah and al-Bay’ Bithaman Ajil Contracts: A Comparative Analysis - Abdul Razak, Dzuljastri; Mydin Meera, Ahamed Kameel (2005)

(untitled)
Home financing takes a large chunk of peoples’ income. As alternatives to conventional interest-based home financing modes, several Islamic modes are currently in existence, the dominant among which are the al-Bay’ Bithaman Ajil (BBA) and the Musharakah Mutanaqisah Partnership (MMP) contracts. The BBA is a murabahah contract, based on buy-and-sell principle while the MMP consists of a musharakah (partnership) contract and an ijarah (rental) contract where the equity of the financier follows a diminishing balance method. Scholars are consensus on the Shari’ah permissibility of the MMP contract, but nonetheless, are not consensus on the permissibility of the BBA contract. Middle Eastern scholars generally disapprove of the BBA, which on the contrary is popular in Malaysia, Indonesia, Brunei etc. This paper is a theoretical paper that compares these two contracts for the financing of assets, from Islamic and economic perspectives. The paper concludes that the MMP has several advantages over the BBA for the customer. Apart from being consensus Shari’ah-compliant, it can be made to avoid interest (riba) totally by means of using some rental or house price index while reducing the cost of homes and the duration of financing. The balance of financing, at any point in time, never exceeds the original price of the asset, unlike under the BBA where it can. When implemented through cooperatives, the MMP can also provide an investment avenue for members while not contributing to macroeconomic problems through the fractional reserve money creation process; and hence is argued to be consistent with the maqāsid al-Sharī’ah. The paper also provides a mathematical derivation note for the MMP.